The roles and functions of life insurance as a financial instrument / Irzan Ismail - Ismail, Irzan (Universiti Teknologi MARA Cawangan Pahang, 2003)
Life insurance is important although not a dominant part of the savings industry. There are other competitors for the long term saving dollar, particularly unit and property trusts, and this has grown in recent years at a much faster rate than the life offices. Our government is attempting to deregulate the financial sector in Malaysia. Banks are opening life office and the life offices are setting up banking subsidiaries. With the move made in recent years towards the regulations of the financial sector, the government has made available more bankers license. This represents the first chance for life offices to become involve in the banking sector and a number of offices responded by applying and obtaining bankers' license. This move by the life offices to the banking area is really a further direction they took with the new products they developed and response to the problems in the past. These new products were more investment oriented and in more direct competitions with the product offered by other financial institutions.